Septic Nonunion in Radius and Ulna in a Dog: Treatment with Orthogonal Plating Associated with Corticospongious Bone Autograft - Ferreira, Danyelle Rayssa Cintra; Luiz Montanhim, Gabriel; Andrade Rangel de Sá, Marina; Maria Izique Diogo, Lúcia; Watanabe Minto, Bruno; Vianêis Farias de Lucena, Dayvid; Castro Moraes, Paola; Gustavo Gosuen Gonçalves Dias, Luís (Acta Scientiae Veterinariae, 2025)
Background: A fracture stabilization strategy must be able to withstand the loads to which the bone will be subjected and be appropriate for the individual patient. Fractures of the radius and ulna are common in dogs; however, the incidence of complications is relatively high. Inadequate repair can result in complications. The treatment of long bone diaphyseal fracture-nonunion is challenging. While considering biological needs, a stable mechanical environment is pertinent for fracture healing. The aim of this study was to describe the treatment of a septic nonunion in the radius and ulna in a large breed dog which had suffered amputation of the contralateral forelimb through stabilization with orthogonal plating and the use of corticospongious bone autograft. Case: A 5-year-old male mixed breed dog, weighing 47 kg, with amputation of the right forelimb had been previously treated for fracture of the left radius and ulna with external immobilization for several weeks. The patient was admitted to our veterinary service 120 days after the initial trauma without effective bone consolidation and refracture after minimal load. The septic nonunion in the left radius and ulna was successfully treated with a custom locked plate 4.5 mm thick on the cranial surface of the left radius, a 3.5 mm thick locked plate on the lateral surface of the left ulna and application of a corticospongious bone autograft from the left iliac crest. Satisfactory return to function and clinical union were achieved at 20 and 75 days postoperatively, respectively. After consolidation, dynamization was performed in 3 stages until complete removal of the implants. The treatment provided an early return of limb function, complete bone consolidation and a good prognosis for the dog. Discussion: The healing of fractures of the radius and ulna can be problematic, and a poor choice of stabilization method can lead to complications such as delayed union, non-union, malunion and angular limb deformities. External immobilization proved to be the least effective technique in the treatment of diaphyseal fractures of the radius and ulna in dogs, even in larger breeds, when compared with the use of external skeletal fixators or plates and screws. The choice of external immobilization may explain the failure of the primary repair in this case. The patient only had this thoracic limb for support, which, in addition to a nonunion, also had osteomyelitis. Thus, rigid stabilization was necessary and, given the biological conditions presented, the use of autograft and antimicrobial treatment against bone infection were favorable for bone repair. Bone grafts have many functions, including improving the biological repair of skeletal defects and reducing time to healing in delayed unions and non-unions, as they stimulate early bridging callus formation. It is already known that to maximize the treatment against infection, bone vascularization in the focus must be present, in such a way, the use of autograft was again justified. Constructions with dual bone fixation (radial and ulnar) allow a significant increase in resistance to axial compression and caudocranial flexion when compared to the use of a radial plate alone and perform better under load-to-failure cycles than other constructions. The use of 2 plates in the present case was considered essential, due to the characteristics of the fracture and the patient. In this way, it was possible to achieve successful treatment by restoring limb functions, such as support and ambulation in a short period of time. Keywords: bone plates, complications, dynamization, fracture healing, osteomyelitis.